An unusual double fungal infection of the bladder due to Candida and Cladosporium - G.V. KandaSwamy; B. Viswaroop; A. Elangovan; M. Arul; S.V. Kandasami; G. Gopalakrishnan (African Journal of Urology, 2015)
Fungal cystitis is usually associated with candida species. Most of the cases are asymptomatic and often due to contamination. Following, we describe the case of a young diabetic lady who presented with severe bladder storage symptoms and persistent sterile pyuria. As candida was isolated from the urine, a diagnosis of fungal cystitis was made. Imaging showed a duplex kidney with complete duplication of the ureters on both sides as well as a contracted bladder with small capacity and bilateral grade-3 reflux into the lower-pole moieties. In view of an increasing severity of the symptoms despite an appropriate treatment, it was decided to augment the bladder. The inflamed bladder wall was excised during augmentation. Tissue culture revealed cladosporium.